Victorian Poetry and Contemporary Issues - Hueso-Vasallo, Manuel (My University, 2025)
As part of the coursework within the mandatory subject “Literatura Inglesa III (Poesía)”, taught in the final year of the degree in English Studies at the University of Málaga, students were asked to analyse the poems here. These poems are all from the Victorian era (1837-1901). Students were asked to carefully read these poems and to transform them into contemporary versions of themselves. They were required not to alter the style or themes of the poems but to ‘update’ them so that they represent what concerns they might have as related to these topics. This exercise (carried out in English, as the subject is taught in this language) had as its aim to show students the continuity of literary themes, the relevance and impact of poetry when commenting social causes and, furthermore, to grant them a wider understanding of rhythm and rhyme, as well as an insight into the difficulties of writing poetry. The exercise was positively received by students and those who voluntarily participated in it alleged that it had been helpful for their overall understanding of the subject.
Keywords: Literatura inglesa - S.XIX; Victorian poetry; British poetry